Management capacity building and digital market access expansion strategy for BUMDes clustering optimization - Rusmiyatun, Rusmiyatun; Arini, Anes; Febriani, Siska; Hafizhuddin, Abid; Tri W, Talita Erina (Community Empowerment, 2025)
BUMDes Dadirejo possesses significant economic potential through its four business units, yet its development is hindered by limited marketing access and low human resource capacity in financial management. This community service project aims to elevate the BUMDes clustering status from the "developing" (berkembang) category to "independent" (mandiri) through workshops and continuous mentoring. The interventions include digital marketing management training (Instagram and TikTok), e-catalog registration for market expansion, and the standardization of financial reports, covering balance sheets, income statements, statements of changes in equity, and cash flow statements. Results show that the BUMDes management achieved an 85% mastery level in financial reporting. Furthermore, the provision of marketing equipment grants successfully encouraged the formation of new business units and strengthened the sales infrastructure. This strategy proved effective in enhancing accountability and market reach, serving as a key step toward achieving the criteria for an Independent BUMDes.